USING THINK-TALK-WRITE STRATEGY IN TEACHING WRITING AN ANALYTICAL EXPOSITION TEXT - Ita As’ar Muna; Zulfadli A. Aziz; Kismullah Abdul Muthalib (Universitas Syiah Kuala, 2020)
This research was conducted to know the effect of Think-Talk-Write strategy on the students’ writing analytical exposition improvement and to know the students’ responses toward the use of this strategy in teaching writing an analytical exposition text. This is a quasi-experimental research in which the samples were taken from two classes, experimental class (XI-IPA F) which consisted of 34 students and control class (XI-IPA G) which consisted of 36 students. The instruments of this research were pre-test and post-test. The result showed that the mean scores of pre-test in the experimental class was 61.47, while the mean score of post-test in the experimental class was 76.67. Moreover, both scores were analyzed by comparing the z-z-score of pre-test and post-test in the experimental class. The result of the z-test was -11.09 at the level significance 5% with assumption if the z-score is beyond -1.96 and 1.96, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Furthermore, the result of the questionnaire showed that the students gave positive responses toward the implementation of Think-Talk-Write strategy on teaching writing analytical exposition text where 57% of students strongly agreed and 40% of students agreed with the implementation of Think-Talk-Write strategy. In conclusion, the implementation of Think-Talk-Write strategy could improve the students’ ability to write an analytical exposition text.